Análise das transformações sociais e ambientais em um processo de ocupação litorânea : o caso do município de Lucena / PB - Fernandes, Luis Jorge Monteiro (2006)
It was aimed in the present work to bring questions forwards on the relations man/Nature, in an attempt to understand the processes related to exploitation of environmental resources. It was also investigated the spatial modifications and social relations at the littoral area where tourism is deemed as the threshold of land-use and under occupancy. This way, it was chosen for this study the coastal plain of the municipality of Lucena, on the northern littoral of Paraíba state. That plain is a typical geomorphologic formation of Northeast Brazil, whose geographical localization and natural and cultural resources, like the 16 km long beaches, constituted by sand dunes, estuaries, religious sanctuaries, population s kind hospitality, among other features, turned that region into a highly popular tourist place, attracting the most different interests from the agents of urban space formation. The occupancy of the area occurred in two distinct periods, which generated the need to analyze the former and current processes of occupancy. The first process took place between 1970 and 1980, when socio-spatial transformations originated from the Pro-álcool governmental programme was settled on coastal tablelands and attracted peasant farmers on search of better life conditions. The second period of occupancy took place in a speed that had not yet been noticed, starting in 1990 through stimuli from the state government by implementing the local infrastructure, mainly the transport system, as roads were built and a ferry-boat was introduced for a shorter and quicker link of Lucena to neighbour cities, besides to open a new space for tourism and for second residence. The urban sprawl in the area has been badly planned, causing many different kinds of social and environmental negative impacts. In loco surveys performed in the present work showed that the most relevant problems in the study area are due to lack of sustainable employment and income programmes, and to negligence on preservation and conservation of natural resources, worsened by deficits in services and urban equipment. After identifying problems and through application of Analytic Hierarchy Process (AHP), a proposal of environmental planning was elaborated for the area, aiming the presentation of actions that could be carried out to reverse the critical social and environmental situation experienced by local population